Proportional Assist Ventilation for Minimizing the Duration of Mechanical Ventilation (the PROMIZING study): update to the statistical analysis plan for a randomized controlled trial - Karen J. Bosma; Myriam Lafreniere-Roula; Arlene Jiang; Anna Heath; Yongdong Ouyang; Kaitlyn Wade; Pingzhao Hu; Karen E. A. Burns; Claudio M. Martin; Yoanna Skrobik; Sorcha Mulligan; Kevin E. Thorpe; et al. (Trials)
Abstract Background We previously published the protocol and statistical analysis plan for a randomized controlled trial of Proportional Assist Ventilation for Minimizing the Duration of Mechanical Ventilation: the PROMIZING study in Trials ( https://doi.org/10.1186/s13063-023-07163-w ). This update summarizes changes made to the statistical analysis plan for the trial since the publication of the original protocol and statistical analysis plan. Methods/design The Proportional Assist Ventilation for Minimizing the Duration of Mechanical Ventilation (PROMIZING) study is a multi-center, open-label, randomized controlled trial designed to determine if ventilation with proportional assist ventilation with load-adjustable gain factors will result in a shorter duration of time spent on mechanical ventilation compared to ventilation with pressure support ventilation for patients with acute respiratory failure. The statistical analysis plan for the trial was incorporated into the original publication of the protocol in Trials ( https://doi.org/10.1186/s13063-023-07163-w ) and was based on version 5.0 of the study protocol and version 1.0 of the statistical analysis plan (SAP), which included plans for both frequentist and Bayesian analyses. We have since updated the SAP to refine the Bayesian analysis plan, update the multistate model diagram, and include plans for a cluster analysis to determine if there is heterogeneity of treatment effect. This update summarizes the changes made and their rationale and provides a refined SAP for the PROMIZING trial with additional background information, in adherence with guidelines for the prospective reporting of SAPs for randomized controlled trials. Trial registration ClinicalTrials.gov Identifier: NCT02447692 prospectively registered May 19, 2015.